2021
DOI: 10.3390/met11020182
|View full text |Cite
|
Sign up to set email alerts
|

Additive Manufactured 316L Stainless-Steel Samples: Microstructure, Residual Stress and Corrosion Characteristics after Post-Processing

Abstract: Additive manufacturing (AM) is a relatively new manufacturing method that can produce complex geometries and optimized shapes with less process steps. In addition to distinct microstructural features, residual stresses and their formation are also inherent to AM components. AM components require several post-processing steps before they are ready for use. To change the traditional manufacturing method to AM, comprehensive characterization is needed to verify the suitability of AM components. On very demanding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…This has been observed elsewhere [14], where the tensile yield strength also started to drop when specimens were reduced in section thickness, and a similar phenomenon could be the reason. When adding surface treatments to this loading condition, sandblasting supposedly creates a work-hardened surface, which should improve the properties of the surface [29,30], but the overall effect on compressive peak strength is limited as the blasting effect is normally shallow. It is suggested that the dislocation hardening of the bulk is still predominant in determining the overall compressive response, as seen by the only 0.85% increase in average peak strength from Sets A→C, whereby the overall change in buckling behavior is not prominent.…”
Section: Discussionmentioning
confidence: 99%
“…This has been observed elsewhere [14], where the tensile yield strength also started to drop when specimens were reduced in section thickness, and a similar phenomenon could be the reason. When adding surface treatments to this loading condition, sandblasting supposedly creates a work-hardened surface, which should improve the properties of the surface [29,30], but the overall effect on compressive peak strength is limited as the blasting effect is normally shallow. It is suggested that the dislocation hardening of the bulk is still predominant in determining the overall compressive response, as seen by the only 0.85% increase in average peak strength from Sets A→C, whereby the overall change in buckling behavior is not prominent.…”
Section: Discussionmentioning
confidence: 99%
“…Post-processing in combination with process control and optimization (and quality assurance) are addressed from different perspectives and for different materials and AM methods in [6][7][8].…”
Section: Contributionsmentioning
confidence: 99%
“…In very demanding corrosive atmospheres, the question is whether AM lowers or eliminates the risk of stress corrosion cracking (SCC) compared to welded 316L components. The authors of [8] concentrate on post-processing and its influence on the microstructure, and surface and subsurface residual stresses. The immersion tests with four-point-bending in an 80 • C magnesium chloride solution for SCC showed no difference between the AM and reference samples, even after a 674-h immersion [8].…”
Section: Contributionsmentioning
confidence: 99%
“…Additive manufacturing (AM) technologies developed in the last two decades have been aimed mainly at producing complex geometrics with minimal machining finishes using powder bed fusion (PBF) technologies, mostly selective laser melting (SLM) and electron beam melting (EBM) [1][2][3][4][5][6][7][8][9][10][11][12]. However, these relatively expensive PBF technologies do not adequately address the need to produce large components with less complicated geometrics at affordable production costs [13,14].…”
Section: Introductionmentioning
confidence: 99%